2008
DOI: 10.1017/s1368980007001486
|View full text |Cite
|
Sign up to set email alerts
|

Maize meal fortification is associated with improved vitamin A and iron status in adolescents and reduced childhood anaemia in a food aid-dependent refugee population

Abstract: Objective: To assess changes in the Fe and vitamin A status of the population of Nangweshi refugee camp associated with the introduction of maize meal fortification. Design: Pre-and post-intervention study using a longitudinal cohort. Setting: Nangweshi refugee camp, Zambia. Subjects: Two hundred and twelve adolescents (10-19 years), 157 children (6-59 months) and 118 women (20-49 years) were selected at random by household survey in July 2003 and followed up after 12 months. Results: Maize grain was milled an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Of these, 121 [25-145] studies were on infants and children and 79 [146-224] were on women, while one study had both women and children as their study population [33] (Figure 2). Furthermore 125 [25-28,30,32-39,41-44,47,48,51,53],[54,56,59,60,62,63,65-73,75-77],[81-83,85,86,88-90,92,93,95-104,107-109],[111-117,119-127,129,130,132-136,139-144,223,225-228] of these trials were RCTs; the rest were quasi-experimental [46,55,61,74,78,87,91] and before-after studies [29,31,40,45,49,50,52,57],[58,79,80,84,94,95,105,131],[137,138,149,150,153,157,159-169,172],[174,177,181,183-186,189-191,193,195-…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 121 [25-145] studies were on infants and children and 79 [146-224] were on women, while one study had both women and children as their study population [33] (Figure 2). Furthermore 125 [25-28,30,32-39,41-44,47,48,51,53],[54,56,59,60,62,63,65-73,75-77],[81-83,85,86,88-90,92,93,95-104,107-109],[111-117,119-127,129,130,132-136,139-144,223,225-228] of these trials were RCTs; the rest were quasi-experimental [46,55,61,74,78,87,91] and before-after studies [29,31,40,45,49,50,52,57],[58,79,80,84,94,95,105,131],[137,138,149,150,153,157,159-169,172],[174,177,181,183-186,189-191,193,195-…”
Section: Resultsmentioning
confidence: 99%
“…A total of 34 studies were identified that reported outcomes on children [36-38,43,46,47,50,61-64],[67-69,71-76,82,86,87,92,93,98],[102,105,115,117,118,121,122,130]. Three of these were before-after studies and the rest were RCTs and quasi-experimental studies.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps more importantly, studies differed in their definition of what constituted ‘recovery’ from malnutrition . While similar definitions of anaemia were used, some studies assessed ‘any’ anaemia and some examined severe, moderate and mild anaemia, with a subset of authors stratifying by age . This points towards a need for consensus on the definition of ‘anaemia’ stratified by age groups and of ‘recovery rate’ stratified for mild‐to‐moderate and severe malnutrition, to facilitate generalisability and comparability of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of improved CSB (i.e. Super Cereal) to the general ration in all five camps during 2010–2011 may also have contributed to reductions in anaemia [49]. Unfortunately, despite the best efforts of the researchers it was not possible to confirm the exact implementation dates for these activities, nor to what extent a combination of these interventions were consistently implemented over a specific time period.…”
Section: Discussionmentioning
confidence: 99%